2021
DOI: 10.1002/jgm.3367
|View full text |Cite
|
Sign up to set email alerts
|

Profiling T cell receptor β‐chain in responders after immunization with recombinant hepatitis B vaccine

Abstract: Background: T cells with edited T cell receptor β-chain variable (TRBV) are involved in the immune response to recombinant hepatitis B surface antigen (rHBsAg) vaccine and the production of hepatitis B surface antibody (HBsAb). The immune repertoire (IR) profile and mechanism of vaccination positive responders (VPR) with rHBsAg are not fully understood.Methods: The IR of six VPRs (HBsAb+, HbsAg-) with rHBsAg vaccination was established by the high throughput sequencing technique and bioinformatics analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 29 In our previous study, we reported the diversity and distribution characteristics of the IR (TRB) based on the V(CDR3)J of TRBV with small cases, and there are no significant differences between the subjects with and without responding to HepB vaccination. 18 However, the Shannon index based on CDR3 is significantly higher in the HepB vaccine responders compared to that in non-responders. Similarly, the CF100 is significantly lower in responders.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 29 In our previous study, we reported the diversity and distribution characteristics of the IR (TRB) based on the V(CDR3)J of TRBV with small cases, and there are no significant differences between the subjects with and without responding to HepB vaccination. 18 However, the Shannon index based on CDR3 is significantly higher in the HepB vaccine responders compared to that in non-responders. Similarly, the CF100 is significantly lower in responders.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, the raw sequence was screened, and the low quality sequences were deleted, the sequencing background was filtered 17 and the international ImMunoGeneTics (IMGT) database ( www.imgt.org ) was used as standard reference sequences and the sequences obtained were compared with the IMGT database in the present study, please refer to our previous report for more detailed steps. 18 …”
Section: Methodsmentioning
confidence: 99%
“…According to current research, the recipient’s response to the hepatitis B vaccine may be influenced by their T-cell immunity. For instance, the edited T-cell receptor-chain variable was linked to the immune response of healthy vaccinees to recombinant hepatitis B surface antigen (rHBsAg) as well as the production of hepatitis B surface antibody (HbsAb) ( 88 ). Circulating follicular helper T cells (cTfh) and subsets were shown to be involved in the immune response to hepatitis B vaccine injection in vitro , and the CXCR3-Tfh cell subset was preferentially activated when HBsAg stimulated PBMCs.…”
Section: T Cells and Measures Of Hbv-mtct Preventionmentioning
confidence: 99%
“…Previous work has shown that FAS is associated with an increase in levels of markers related to immunity, such as B lymphocyte response markers, innate immune proinflammatory pathways (14) , antigen processing and presentation markers, nuclear factor-k-gene binding signalling pathways, tumor necrosis factor signalling (15) , interleukin-8 (16) and interleukin-4 (IL-4) (17,18) . Previous research has also revealed a positive association between immune markers and hepatitis B vaccine response, including T-cell receptor β-chain variable (19) , NDRG1-expressing myeloid dendritic cell-2, CDKN1C-expressing myeloid dendritic cell-4 (20) , chemokine (C-X-C motif) ligand 12, https://doi.org/10.1017/S000711452200229X Published online by Cambridge University Press Accepted manuscript interleukin-27 (21) , interferon-γ, interleukin-2 (22) , interleukin-17, interleukin-18 (23) and IL-4 (22,24,25) . Among the above immune markers, we noticed that IL-4 is related to both FAS and hepatitis B vaccine response.…”
Section: Introductionmentioning
confidence: 96%